SACRED CURRENTS AND TAINTED WATERS: AN ECOCRITICAL READING OF THE RIVER GANGA - Sharma, Dr. Shivangani (International Journal of Research -GRANTHAALAYAH, 2025)
The River Ganga occupies a unique position in Indian cultural, spiritual, and ecological consciousness. Revered as a divine mother and a source of spiritual liberation, the Ganga simultaneously stands today as one of the most polluted rivers in the world. This paper offers an ecocritical reading of Raja Rao’s On the Ganga Ghat to examine how the river functions as a sacred, living presence within Hindu cosmology while also revealing the contradictions inherent in contemporary attitudes toward nature. Drawing upon the theoretical frameworks of deep ecology and eco-spiritualism, particularly the ideas of Arne Naess and Thomas Berry, the paper explores the tension between reverence and exploitation, faith and environmental neglect. Through Rao’s spiritually charged narratives set in Benares, the study highlights the urgent need to reclaim an ecological ethics grounded in spiritual awareness.